2015 IEEE International Conference on Service Operations and Logistics, and Informatics (SOLI) 2015
DOI: 10.1109/soli.2015.7367594
|View full text |Cite
|
Sign up to set email alerts
|

The critical flaw in the implementation of GPS tracking system in express bus industry

Abstract: Land Public Transport Commission (SPAD) in Malaysia has made it mandatory that GPS tracking systems installed in every express buses since 2008 so that the speed can be monitored and recorded based on real-time. Nonetheless, the effectiveness of the system is under question when Malaysia was startled by a series of bus accidents each killed close to 10 lives while several others were seriously injured. This study is undertaken to identify the critical flaw in the implementation of the GPS monitoring system and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A study on GPS tracking system for express bus [12], [4] has recommended an advisory intelligent system adaption device [15] called electronic speed supervisor (ESS) to be installed in express buses as a way to disclose the real-time speed to the passengers due to the critical flaw found in the express bus GPS tracking system for fleet management. Their study found that the speed is only recorded for postaccident analysis [12], [13]. They also recommended the features listed in table 2.…”
Section: Introductionmentioning
confidence: 99%
“…A study on GPS tracking system for express bus [12], [4] has recommended an advisory intelligent system adaption device [15] called electronic speed supervisor (ESS) to be installed in express buses as a way to disclose the real-time speed to the passengers due to the critical flaw found in the express bus GPS tracking system for fleet management. Their study found that the speed is only recorded for postaccident analysis [12], [13]. They also recommended the features listed in table 2.…”
Section: Introductionmentioning
confidence: 99%